Peran Manajemen Sumber Daya Manusia dan Orientasi Pasar terhadap Kinerja Industri Sarung Tenun Donggala di Sulawesi Tengah - Zahara, Zakiyah; Darman, . (Universitas Brawijaya, Indonesia, 2015)
The aim of this study is to analyze the effect of human resources management whichis supported by a market orientation in improving the economic performance of creativecraft woven sarongs of Donggala in Central Sulawesi. Therefore, the population in theresearch is the creative craft industries Donggala sarong scattered at 1 (one) district and 1(one) in the city of Central Sulawesi, namely Donggala and Palu are 52 industries. Thepopulation was taken a sample of 31 industries, through random sampling method. Theanalytical tool used is path analysis. The study found that human resource management hasno effect (sig. 0.098) directly on the performance of the creative craft industry of Donggalasarong. Human resource management has a significant effect (sig. 0.000) towards marketorientation and market orientation effect (sig. 0.010) on the performance of the creativecraft industry of Donggala sarong. Training programs, empowerment and performance assessmentcarried out by the craft creative industries Donggala sarong affect the attitude ofmarket orientation, which in turn have an impact on improving the performance of thecreative industries craft of Donggala sarong.